UJI BAKTERI Escherichia coli (Coliform) PADA CINCAU HITAM YANG DIJUAL PEDAGANG MINUMAN DI SEKITAR KAMPUS UNIVERSITAS RIAU SEBAGAI RANCANGAN LKPD PADA MATERI EUBACTERIA SMA KELAS X - Robi Komari AA; Irda Sayuti; Zulfarina Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to know the total Coliform bacteria and the presence of Escherichia coli bacteria in black grass jelly sold around the campus of Universitas Riau, as well as to know the potential of the research results to be used as worksheet design on eubacteria concept of the first year students in senior high school. The study was conducted at the microbiology laboratory of medicine faculty and the Biology Education Campus, Faculty of Teacher Training and Education Universitas Riau. The sample used was black grass jelly sold by beverage traders around the Riau University campus with a purposive random sampling method based on predetermined criteria.The sample used was black grass jelly which is sold by street drink vendors around Universitas Riau area. The test of Escherichia coli (Coliform) bacteria in black grass jelly used Most Probable Number (MPN) method with contains 3 test stages, namely Presumtive Test, Confirmation Test, Complete Test by using different growth media and incubated at 37oC for 2x24 hours. The results showed 8 of the 8 samples tested did not meet the microbial contamination requirements and there were Escherichia coli bacteria in the 3 samples studied. The highest total Coliform bacteria was found in sample B in location 2 (Bangau Sakti street), while the lowest total Coliform was found in sample A in location 2 (Bangau Sakti street) and sample A in location 3 (HR Subrantas street). All samples tested had a total Coliform that exceeded the food safety requirements set by BPOM RI. there were Escherichia coli bacteria in the 3 samples studied. Then, this results can be used as worksheet design (LKPD) on the eubacteria concept of the first year students in senior high school.Key Words: Black Grass Jelly, Coliform, Escherichia Coli, MPN